Breed and environmental effects on lamb production in Nigeria - Buvanendran, V.; Adu, I.F.; Oyejola, B.A. (Cambridge University Press, 1981)
Knowledge of the extent of variation due to non-genetic factors is vital to eliminate environmental effects and improve the efficiency of selection in sheep. Two indigenous breeds, the Udah and the Yankasa and crosses of these with exotic breeds were evaluated for lamb weights at birth, 3 months and 6 months of age, and for adult ewe weight. Crossbred lambs were significantly (P